Affirmative Action Initiatives Around the World - Jenkins, Laura Dudley; Moses, Michele S (International Higher Education, 2014)
Affirmative action policies to increase the number of underrepresented students in higher education have expanded globally in the last quarter-century. Gender is the most prominent policy target. Institutions of higher education and governments have increasingly adopted race-neutral or multifaceted affirmative action policies, in response to legislative threats, legal challenges or social criticism.